2021
DOI: 10.1590/1983-1447.2021.20200087
|View full text |Cite
|
Sign up to set email alerts
|

The work of the nursing team in the operating room and the health-related damages

Abstract: Objectives: to analyze the work of the nursing team in the operating room and the physical, psychological, and social damage related to occupational health. Methods: quantitative study conducted from November 2017 to January 2018 in the operating room of a university hospital. The sample consisted of 160 nursing workers who responded to the Work-Related Damage Assessment Scale. Data were analyzed using the Student’s t test, One-Way analysis of variance (ANOVA) followed by Pearson’s chi-square test. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Mitigating or eliminating these environmental factors can increase employee satisfaction and retention [33]. As in our study, also Kulczycka, Żarnowska, Stychno et al found that there is a relationship between the hourly dimension of work and its impact on workload as an occupational risk factor, which is also related to the number of surgical procedures and preparatory activities required to perform them [34]. The data collected by Kulagowska in a group of 398 nurses working in different types of operating rooms in 11 public hospitals prove that the main source of problems is the organization of work, technical factors, working means, workspace, and the nurses' knowledge of harmful and burdensome factors, ways to reduce their impact and/or protect themselves from them.…”
Section: Discussionsupporting
confidence: 75%
“…Mitigating or eliminating these environmental factors can increase employee satisfaction and retention [33]. As in our study, also Kulczycka, Żarnowska, Stychno et al found that there is a relationship between the hourly dimension of work and its impact on workload as an occupational risk factor, which is also related to the number of surgical procedures and preparatory activities required to perform them [34]. The data collected by Kulagowska in a group of 398 nurses working in different types of operating rooms in 11 public hospitals prove that the main source of problems is the organization of work, technical factors, working means, workspace, and the nurses' knowledge of harmful and burdensome factors, ways to reduce their impact and/or protect themselves from them.…”
Section: Discussionsupporting
confidence: 75%